Analysis of Ibn Abi Hatim Al-Razi's Assessment of Hadith Narrators - Yusup Muhidin; Dadah, Dadah (al-Afkar, Journal For Islamic Studies, 2025)
This paper aims to explain the assessment of Ibn Abi Hatim Al-Razi and the systematics of the book Al-Jarhu wata'dil. With the library research method, sourced from books and scientific journals with an analytical descriptive approach, it is expected to provide accurate information on Ibn Abi Hatim's assessment of hadith narrators. The maintenance of the authenticity of hadith is an important requirement for Islamic teachings. The nuqqad such as Ibn Abi Hatim conducted an assessment of the narrators in maintaining the validity of the hadith from error and forgery. Effort is the way to find out his authenticity and kedhabitan. The result is the classification of marathib alfadz and mustholahat specifically maqbul and mardud narrators in Al-Jarh wa ta'dil is the result of the quality of the narrator.